PENGARUH GREEN MARKETING DAN BRAND IMAGE TERHADAP MINAT BELI SKINCARE AVOSKIN (STUDI PADA MAHASISWA DI KOTA SURABAYA) - Ardiana, Ika Nopita; Rafida, Veni (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to determine the effect of Green Marketing and Brand Image on Intention to Buy Avoskin Skincare (Study on College Students in Surabaya City). This research uses descriptive quantitative. The population in this study were students aged 18-25 years in the city of Surabaya using the Purposive Sampling technique and using the Lameshow formula for sample calculations with a minimum of 100 samples and 105 samples were used for this study. Data was collected via the Google form and measured using a Likert scale using multiple linear regression analysis using the IBM 25 version of SPSS software. The results of this study indicate that there is no significant effect of green marketing on purchase intention and there is a partial effect of brand image on purchase intention. Meanwhile simultaneously Green Marketing and Brand Image have a joint effect on Purchase Intention. Keywords: Green Marketing, Brand Image, Purchase Intention